Quantitative Estimation of Piperine in Trikatuku Curanam - JEGANATHAN, N.S.; KANNAN, K. (Asian Journal of Chemistry, 2010)
Curanams are important group of formulations used by ayurvedic and siddha physicians to treat various types of diseases. Trikatuku curanam which is used for the treatment of various types of gastric disorders is prepared as per the formula given in Siddha Formulary of India, Part I, First Edition, by procuring all the drugs from the local market. In the present study, an attempt has been made to develop a HPTLC method of quantitative estimation of piperine in laboratory prepared authentic formulation and a marketed formulation of Trikatuku curanam. The two formulations were subjected to methanol and ethyl acetate extractions by soxhylation. Piperine was quantified in the above two extracts by using high performance thin layer chromatography. The detection and quantification was performed at a wavelength of 340 nm. The laboratory formulation was found to contain 1.491 % of piperine while the commercial formulation shows 1.904 % of Piperine in methanol extracts. The laboratory formulation was found to contain 1.820 % of piperine and commercial formulation shows 2.432 % of piperine in ethyl acetate extracts. The method was validated by carrying out linearity, percentage recovery and reproducibility results. Linearity studies indicated that piperine was in the linear range of 30-105 ng while the % recovery studies revealed a recovery of 98.73 % w/w, thus proving the accuracy and precision of the analysis.